Developing skills in higher education for post-pandemic work. (2nd October 2021) - Bayerlein, Leopold; Hora, Matthew T; Dean, Bonnie A; Perkiss, Stephanie
ABSTRACT: Many white-collar workplaces have changed substantially because of the pandemic. This paper examines how the rise of technology-based distributed work arrangements impacts on the knowledge, skills and competencies that higher education graduates must possess to be successful in post-pandemic white-collar work environments. In addition, this paper examines prior literature to identify digital forms of Work Integrated Learning as a mechanism through which higher education providers can assist graduates in their post-pandemic transition from university to the workplace.